Politik Pelembagaan Syariat: Strategi Dan Argumentasi PPP, PBB, Dan PKS Di Sidang Tahunan MPR 1999-2002 - Muhammad Ansor (Universitas Islam Negeri Mataram, 2005)
Of the classical problems in the discourse of Islam and politics is controversy on interpretation of Islamic Syarî‘ah, and there is no single or only one true definition of the term. The controversy is going worse when some groups of Muslim—with or without intervension and support of the ruling power—insist to have their opinion the true one and should be followed by others. This article is comparing the strategy and arguments used by the three Islam-based parties—PPP, PBB, and PKS—in the parliament of Indonesia when they respond the discourse of applying Islamic Syarî‘ah in Indonesia. They share opinion that the application of Islamic Syarî‘ah through state is a duty of every Muslim, but they differ one another in the way or strategy of realizing and making that come true. Different from PPP and PBB that struggle for adopting the Jakarta Carter into Indonesian 1945 Constitution, PKS (with PAN) suggest adopting Medina Carter. When the majority of parliament members refuses both suggestions, the three parties also take different ways responding the refusal. While PPP can understand the refusal and explicitly agree to no-amendment on the article 29 of Indonesian 1945 Constitution, PBB and PKS declare to be abstains. The controversy indicates the difficulty of unifying Muslim opinion and strategy relating to the how to position Islam in the context of state. The phenomena that occurs between the supporting and the refusing group is not only in terms of positivization of Islamic Syarî‘ah, but also in applying Islam. It ranges from the issues of struggle strategy to the decision of aspects of Syarî‘ah that can be adopted in or made positive law.